Alterations in Tau Metabolism in ALS and ALS-FTSD - Strong, Michael J.; Donison, Neil S.; Volkening, Kathryn (Frontiers in Neurology, 2020)
There is increasing acceptance that amyotrophic lateral sclerosis (ALS), classically considered a neurodegenerative disease affecting almost exclusively motor neurons, is syndromic with both clinical and biological heterogeneity. This is most evident in its association with a broad range of neuropsychological, behavioral, speech and language deficits [collectively termed ALS frontotemporal spectrum disorder (ALS-FTSD)]. Although the most consistent pathology of ALS and ALS-FTSD is a disturbance in TAR DNA binding protein 43 kDa (TDP-43) metabolism, alterations in microtubule-associated tau protein (tau) metabolism can also be observed in ALS-FTSD, most prominently as pathological phosphorylation at Thr175 (pThr175tau). pThr175 has been shown to promote exposure of the phosphatase activating domain (PAD) in the tau N-terminus with the consequent activation of GSK3β mediated phosphorylation at Thr231 (pThr231tau) leading to pathological oligomer formation. This pathological cascade of tau phosphorylation has been observed in chronic traumatic encephalopathy with ALS (CTE-ALS) and in both in vivo and in vitro experimental paradigms, suggesting that it is of critical relevance to the pathobiology of ALS-FTSD. It is also evident that the co-existence of alterations in the metabolism of TDP-43 and tau acts synergistically in a rodent model to exacerbate the pathology of either.